1975
DOI: 10.1111/j.1469-7610.1975.tb01872.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Institutional Rearing on the Behaviour Problems and Affectional Relationships of Four‐year‐old Children

Abstract: IT IS known to every student of child development that serious personality defects are said to follow early institutional rearing. The evidence on which this assertion is based is now very out-dated and in need of review. Most English residential nurseries for young children have enormously improved in response to criticisms and bear little resemblance to the grim institutions described by earlier writers. In the nurseries studied by the authors and colleagues the children lived in small mixed age groups, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
194
0
9

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(214 citation statements)
references
References 8 publications
11
194
0
9
Order By: Relevance
“…Drawing upon these studies, Tizard and Rees (1975) reported that at age 4 years, a majority of young children (18/26) who had been raised in residential nurseries in the United Kingdom since birth exhibited aberrant attachment behavior. A group of 8 children were described as emotionally withdrawn and unresponsive, and another group of 10 children were indiscriminate, attention seeking, and socially superficial.…”
Section: Clinical Perspectives On Attachmentmentioning
confidence: 99%
“…Drawing upon these studies, Tizard and Rees (1975) reported that at age 4 years, a majority of young children (18/26) who had been raised in residential nurseries in the United Kingdom since birth exhibited aberrant attachment behavior. A group of 8 children were described as emotionally withdrawn and unresponsive, and another group of 10 children were indiscriminate, attention seeking, and socially superficial.…”
Section: Clinical Perspectives On Attachmentmentioning
confidence: 99%
“…Although Tizard and her colleagues (Hodges & Tizard, 1989;Tizard & Hodges, 1978;Tizard & Rees, 1975) found that institutionalized children were able to form attachments with their caregivers after having spent their first few years in institution. it is important to note that the institutions from which Tizard derived her sample reflected far better conditions than the reported conditions in Romanian orphanages (Chisholm.…”
mentioning
confidence: 99%
“…Research on the characteristics of children raised in institutions (Provence & Lipton, 1962;Skeels, 1966;Tizard & Hodges, 1978;Tizard & Rees, 1974,1975 has influenced the criteria for the disinhibited and indiscriminately social type of attachment disorder. In the Tizard and Rees (1975) investigation, for example, 10 of 26 children institutionalized for their first 4 years of life were noted on evaluation at age 4.5 years to have superficial attachments to staff members, with attention-seeking, clinginess, and overfriendly behavior with strangers being notable social characteristics. show selective attachments, a relative lack of selectivity in the persons from whom comfort is sought, and poorly modulated social interactions with unfamiliar persons across a range of social situations.…”
Section: Attachment Disorders and Contemporary Nosologiesmentioning
confidence: 99%